Organizing Professional and Pedagogical Training to Improve English Teachers’ Skills: A Literature Review - URIP SULISTIYO; SEPTU HASWINDY (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2018)
This literature review study aims to address the current issues on English Teachers’ problems in their efforts to develop their professional and pedagogical competence, in Jambi Province, Indonesia. The critical review of relevant studies on the field of professional and pedagogical competence of EFL teachers reveals that there are several topics related to the competences and skills that teachers should have to better improve their teaching practice. In this review, the researchers present what literatures suggested and recommended in the area of teachers’ professional and pedagogical competence and possible training that stakeholders might hold to improve the quality of teachers teaching English both in junior and senior high schools in Indonesia. The relevant articles being reviewed were from Indonesian context as well as International context. This study hopefully can contribute to the betterment of teaching practice of English in Indonesian schools. The following topics are presented in order; teacher’s professional competence, teachers’ pedagogical competence. The domains and dimensions of English teachers’ competence, teachers’ training, and conclusion and suggestions.